RANTAI NILAI AGRIBISNIS KOPI SERTIFIKASI DI KABUPATEN LAMPUNG BARAT - Aisyah Nur Citra Dewi; Bustanul Arifin; Lina Marlina (Lampung University, 2019)
This research aims to analyze certified and non-certified coffee agribusiness value chains found in West Lampung District, analyze the efficiency of certified and non-certified coffee agribusiness value chains and, the formulation of coffee price in the certified and non-certified coffee agribusiness value chains in West Lampung District. The study is conducted in three sub-districts namely Air Hitam, Kebun Tebu and Sumber Jaya. Total respondents coffee farmers are 146 coffee farmers, consist of 85 certified coffee farmers and 61 non certified coffee farmers’ chosen by cluster random sampling method. Total respondents are 20 sellers; consist of 9 group sellers’ collector, 7 local sellers’ collector, 2 wholesalers and 2 exporters chosen by snowball sampling method. Research data was collected in November 2016 to January 2017 and analyzed by qualitative and quantitative analysis. The research result showed that there were three channels in the agribusiness value chain of certified coffee and two channels in the agribusiness value chain of non-certified coffee. Channel three in the agribusiness value chain of certified coffee and channel two in the agribusiness value chain of non-certified coffee have been efficient with formulation process of price certified and non-certified coffee in the agribusiness value chain of coffee in West Lampung, the buyer was a price setter and the seller was as a price taker.Key words: certified coffee, non-certified coffee, value chain